Microarray methods and protocols. - Matson, Robert S., ....- (Boca Raton : CRC, 2009)
Microarray Methods and Protocols provides insight into present and future uses for microarray technology. This book presents an overview of companies providing arrays, the type of arrays available, array construction processes, substrate chemistry, array printing, and quality control. With a focus on nucleic acid microarrays of biomedical relevance and the use of microarrays in drug discovery, the text describes the application of gene expression arrays to identify drug targets for human diseases and to predict possible drug toxicity problems. The relatively new field of protein microarray technology is also discussed, including technical challenges and how they have been overcome.